High efficiency motor design of electric air-suction Seed metering device. Issue 17 (2018) - Xu, Wenqing; Yi, Shujuan; Mao, Xin; Tao, Guixiang
Abstract: In order to improve the working time of the planter.Aiming at the problems of low efficiency and high power consumption of the electric air-suction metering device drive motor, an efficient brushless DC motor is proposed. Based on the calculation of the structural parameters of the brushless DC motor, this machine analyzes the electromagnetic field and electromagnetic performance. A brushless DC motor model was built on the Motor Solve software and simulated. The simulation results show that there is no demagnetization phenomenon at the magnet, and the flux linkage is reasonable. The efficiency point can reach 85% at the rotation speed required by the seeding device.